Programa de integridade na administração pública municipal : institucionalização, conformidade e mudança gradual - Coimbra, Leandro Belisário Ferreira (2023)
The present work has as its theme the integrity programs, considered as mechanisms and procedures destined to assure the conformity of the organizations and their agents to the ethical principles and to the other established norms, in order to face the phenomenon of the corruption. The general objective of this dissertation is to analyze the implementation and functioning of an integrity program in the municipal public administration. The dissertation presents the theoretical foundations about the phenomenon of corruption and its confrontation, local integrity systems and integrity programs, and mobilizes the theoretical framework of the new institutionalism. The analysis of the implementation and operation of a municipal public administration integrity program was based on a case study. Such perspectives motivated the use of different dimensions of analysis: organizational field; isomorphism processes; ceremonialism and other strategic responses; and gradual change. As for the methodological procedure, we opted for qualitative research, through a single instrumental case study, analyzing the integrity program of a large Brazilian municipality. A literature review was carried out on the relevant theme and a case study was carried out through a documentary survey and 11 semi-structured interviews, which were interpreted through content analysis. The research findings reveal the existence of an organizational field in which the federal comptroller (Controladoria-Geral da União) assumes a prominent position in the dissemination of integrity programs. In this scenario, the existence of the three types of isomorphism processes was observed, namely, normative isomorphism, mimetic isomorphism and coercive isomorphism. Responding to institutional pressures, the organization designed a public integrity promotion program aimed at promoting and managing the implementation of integrity programs in its administrative units, through optional membership. The implementation and operation of the tool in the organization show a significant level of actual (acting) compliance with the normative guidelines regarding integrity programs, although in certain aspects it is possible to glimpse the existence of ceremonialism and non-compliance. This implementation, however, has been taking place in stages, and this process is not yet concluded. One cannot disregard the symbolic dimension that exists in the implementation of an integrity program, helping the organization to guarantee its legitimacy in its organizational field. In addition, it is observed that the implementation of the integrity program in the organization provoked a process of gradual change, mainly in layering, by which new practices and rules are introduced on top of or alongside those that already exist. It was possible to notice that the characteristics of municipal public administration impose greater attention to the implementation of programs in local governments, due to aspects such as the fragility of accountability systems. The study collaborates with the discussion on the subject, allowing to broaden the understanding of the implementation and operation of integrity programs in municipal public administration, based on the presentation of new perspectives on the subject and new reflections on the strategic actions necessary to guarantee the proper functioning of such programs. From a theoretical point of view, the investigation is justified due to the recency of the theme, the need to advance studies on tackling corruption in public administration and the gaps in academic production regarding the analysis of integrity programs at the local level. From a practical point of view, the present study is justified due to the dissemination of such programs in the national public sector, which demands the construction of analyzes and critical reflections about their use. It is suggested that further studies continue to analyze the implementation and operation of integrity programs, in order to verify their evolution, as well as seek to verify their effectiveness in fighting corruption.